Website development for cloud-based verification - Nur Amira Azmir (2016)
The main objectives of this report is to provide a comprehensive idea on the web-based simulator component of the PAT (Process Analysis Toolkit) application. It will explain the primary functions that were tasked to be developed for the existing web application. Currently, the two functionalities that were already built on the Web Application include Check Grammar and Verification. The main focus for this phase of the development is to plan to build a web-based process analysis tool to simulate the state space generation in model checking. This refers to the famous data model checker - PAT. The design of the architecture of the web application is constructed based on the simulator in PAT. How the simulation component is built for desktop application is studied and it adds as a crucial step in eventually mimicking the same idea on the web application. The simulation component will require the check grammar functionality that was built previously on the web before it displays the graph. It will also allow users to view individual processes of the graphs and provide information on them. Some ideas in this report include using a JavaScript Graph Library as an anchor to output the graphs. This report will provide the necessary information such as, libraries (Cytoscape.js), web development frameworks used (e.g. MEAN, EdgeJS) to develop the web application. Some visualization is presented to clearly show how these frameworks interact with each other. Eventually, the web-based Simulator will be built to cater the needs of the PAT users and this will then integrate with developed components of Check Grammar and Verification.